Effect of mutations causing overexpression of RNA polymerase alpha subunit on regulation of virulence factors in Bordetella pertussis. - Carbonetti, N H (1994)
In Bordetella pertussis, expression of virulence factors is controlled by the Bvg proteins, which comprise a sensor-regulator two-component signal transduction system. Previously, we described a mutant strain of B. pertussis that had reduced transcription of pertussis toxin and adenylate cyclase toxin genes, while other virulence factors were relatively unaffected. We obtained a B. pertussis clone that repaired the defect in both this strain and an independent mutant strain with a similar phenotype when introduced onto the chromosome by allelic exchange. Further analysis revealed that the mutations were just upstream of the translational start site of the rpoA gene encoding the alpha subunit of RNA polymerase. We confirmed that these mutations were responsible for the mutant phenotype by site-directed mutagenesis. Our hypothesis that these mutations cause an overexpression of rpoA was confirmed by Western immunoblotting and translational fusion analysis. Corroboration of this effect was obtained by overexpressing rpoA on a plasmid in wild-type B. pertussis, which caused the same phenotype as the mutants showed. Conclusions in regard to the identity of the transcription activator of the toxin genes are discussed.